Histone modifications in the regulation of erythropoiesis - Xiuyun Wu; Hongdi Xu; Erxi Xia; Linru Gao; Yan Hou; Lei Sun; Hengchao Zhang; Ying Cheng (Annals of Medicine)
Introduction The pathogenesis of anemia and other erythroid dysphasia are mains poorly understood, primarily due to limited knowledge about the differentiation processes and regulatory mechanisms governing erythropoiesis. Erythropoiesis is a highly complex and precise biological process, that can be categorized into three distinct stages: early erythropoiesis, terminal erythroid differentiation, and reticulocyte maturation, and this complex process is tightly controlled by multiple regulatory factors. Emerging evidence highlights the crucial role of epigenetic modifications, particularly histone modifications, in regulating erythropoiesis. Methylation and acetylation are two common modification forms that affect genome accessibility by altering the state of chromatin, thereby regulating gene expression during erythropoiesis.Discussion This review systematically examines the roles of histone methylation and acetylation, along with their respective regulatory enzymes, in regulating the development and differentiation of hematopoietic stem/progenitor cells (HSPCs) and erythroid progenitors. Furthermore, we discuss the involvement of these histone modifications in erythroid-specific developmental processes, including hemoglobin switching, chromatin condensation, and enucleation.Conclusions This review summarizes the current understanding of the role of histone modifications in erythropoiesis based on existing research, as a foundation for further research the mechanisms of epigenetic regulatory in erythropoiesis.